Battle phase for role playing game - Muhammad Muhaimin, Juhari (2009)
Role Playing Game (RPG) is a popular game genre that usually focused on the in game character development embedded in a fantasy story.Generally the game backbone storyline is circling around the main character and his party,embark on adventurous journey slaying monsters and eventually saving the world.The problem with RPG is the repetition encounter with enemies, making battle phase become easily predictable and soon player will get bored with it.The objective of this project is to develop a working battle phase to demonstrate on how battle of RPG will look like, with integrated artificial intelligence. The rule based Al will heighten the difficulties of game play,and the fun factor, resulting in longer time for player to feel bored.The battle phase developed using Visual C# 2005 with XNA Game Studio 3.0 framework.The result is a RPG with a battle phase and rule based Al in a 2D environment.The integration of Al make the game plays more interesting and fun.Conclusively,the process of battling in RPG was successfully demonstrated and RPG battle phase is more challenging with rule based artificial intelligence.